Ukrainian School on the Way to Quality Education - Ляшенко, Олександр (Educological discourse, 2014)
The article is devoted to the quality of general secondary education system in Ukraine. In the article are discovered the results of participation of Ukrainian students in the International investigation of natural and mathematical education quality TIMSS – 2007 and results of External independent testing 2010 of school graduates. The author underlines the importance of changes in educational content and updating of the standard of education, questioned the advisability of returning to the 11-year period of complete general education.